Female labour force participation in MENA's manufacturing sector: The implications of firm-related and national factors - Ali Fakih; Pascal L. Ghazalian (Institute for the Study of Labor (IZA), 2013)
The Middle East and North Africa (MENA) region falls behind several other geo-economic regions in terms of women's participation rates in the labour market. This paper examines the implications of firm-related and national factors for Female Labour Force Participation (FLFP) rates in manufacturing firms located in the MENA region. The empirical investigation uses data derived from the World Bank's Enterprise Surveys database and applies fractional logit models to carry out the estimations. The results reveal positive implications of many firm-related factors, mainly private foreign ownership and exporting activities, for FLFP rates. National factors, such as economic development and gender equality, are also found to promote FLFP rates. These effects are generally found to be more important for women's overall labour participation rates than for women's non-production labour participation rates.
Keywords: J16; J21; J23; J82; 330; female labour force participation; fractional logit model; manufacturing firms; MENA region